Memento Mori and gerontography. Issue 9 (21st October 2018) - Hepburn, Allan
ABSTRACT: Novels are so often identified with development and Bildung – all implicitly about youthful characters in search of experience – that the representation of old age may be classed as an anti-novelistic phenomenon. In Memento Mori, Muriel Spark focuses on a group of characters over 70 years old in order to weigh the physiological and spiritual dimensions of ageing. Her working notes for the novel, now archived at the University of Tulsa, indicate that she researched her subject by dipping into Adolf Vischer's Old Age: Its Compensations and Rewards (1947) and Alex Comfort's The Biology of Senescence (1956). She reworked a considerable amount of material from these sources into the plot and phrasing of Memento Mori . In this early novel, Spark elaborates a novelistic gerontography, which I define as the textual representation of old age that accounts for a humane, non-scientific experience of age.